2020
DOI: 10.3390/nu12092758
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Intervention through Nutrition Education and Exercise (FINE). A Health Promotion Intervention to Prevent Frailty and Improve Frailty Status among Pre-Frail Elderly—A Study Protocol of a Cluster Randomized Controlled Trial

Abstract: The ageing process has been associated with various geriatric issues including frailty. Without early prevention, frailty may cause multiple adverse outcomes. However, it potentially may be reversed with appropriate interventions. The aim of the study is to assess the effectiveness of nutritional education and exercise intervention to prevent frailty among the elderly. A 3-month, single-blind, two-armed, cluster randomized controlled trial of the frailty intervention program among Malaysian pre-frail elderly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The percentage of older patients in hospitals in the Klang Valley who responded to the MNA-SF questionnaire-which was divided into 3 scores of "Normal" (12)(13)(14), "At Risk" (8)(9)(10)(11), and "Malnutrition" (0-7)-was 27.9% (n=65) normal, 54.9% (n=128) at risk, and 17% (n=40) malnutrition, which is the lowest. Thus, most patients were at risk of malnutrition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of older patients in hospitals in the Klang Valley who responded to the MNA-SF questionnaire-which was divided into 3 scores of "Normal" (12)(13)(14), "At Risk" (8)(9)(10)(11), and "Malnutrition" (0-7)-was 27.9% (n=65) normal, 54.9% (n=128) at risk, and 17% (n=40) malnutrition, which is the lowest. Thus, most patients were at risk of malnutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Other risk factors include the presence of comorbidities [ 7 , 8 ], poor dental status [ 9 ], and inadequate dietary intake [ 7 , 10 , 11 ]; moreover, those living in health care institutions often complain of having poor foodservice experience [ 12 , 13 ]. Older people with malnutrition often find themselves in a state of dependency, having prolonged hospital stays, an increase in infection rate that eventually diminishes their quality of life, and an increase in health care costs and mortality [ 6 , 7 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic interventions for physical frailty have focused on exercise and nutritional supplementation ( Dent et al, 2019 ; Mohd Suffian et al, 2020 ; Zheng et al, 2022 ). The ICFSR-CPGs ( Dent et al, 2019 ) recommend a multi-component physical activity programme as first-line therapy for physical frailty in older adults, and protein/caloric supplementation when there is weight loss or malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Our study does not support the combined strategies being better than either strategy alone, and suggests that long-term (ie, beyond 6 months) positive effects on frailty are 4 or have involved intensive supervised activity several times a week. 43 There are several trials of similar combinations of interventions yet to be published, [44][45][46][47][48][49][50] which are needed to further clarify the effectiveness of such interventions in preventing and reversing frailty. 51 Applying the NNT to our data showed that for one pre-frail person to become robust in the SC group at 6 months after the intervention, 6 (95% CI 3-19) would need to be treated, while for the SAYGO group, 9 (4-289) would need to be treated.…”
Section: Discussionmentioning
confidence: 99%